Model Pembelajaran Interaktif dalam Menulis Apresiasi Sastra di SMAN 1 Wates Kabupaten Kediri - Derana, Ganes Tegar (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
Ideally, literature learning is developed through an active and interactive approach so that students are directly involved in the learning process. However, in fact, learning practices are often trapped in conventional approaches that do not actively involve students. This study aims to (1) examine the interactive learning model in writing activities and literary appreciation and (2) its impact on student involvement. The study was conducted using a qualitative descriptive approach. Data were collected through observation, interviews, and analysis of learning documents with the research location at SMAN 1 Wates, Kediri Regency. The results of the study showed that interactive learning was able to increase students' active participation. Students looked more enthusiastic, involved in discussions, and demonstrated writing skills that were more sensitive to the aesthetic values ​​and meaning of literary works. This model not only conveys knowledge, but also shapes students' perspectives and sensitivity to life through literature. Transformative literary learning allows students to develop self-expression, empathy, and deep appreciation of literary works. These findings emphasize the importance of learning strategies that involve emotions, critical thinking, and students' personal experiences so that literary learning becomes more alive, meaningful, and relevant to reality.